2009
DOI: 10.1039/b904439f
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increasing hydrophobicity on the self-assembly of amphipathic β-sheet peptides

Abstract: Peptide self-assembly processes are central to the etiology of amyloid diseases. Much effort has been devoted to characterizing amyloid structure and the mechanisms of peptide self-assembly leading to amyloid. It has been proposed that aromatic side-chain interactions play a central role in early self-assembly recognition events, but this contention remains somewhat controversial. Recent studies have indicated that in some amyloid peptides, aromatic residues can be exchanged for other hydrophobic residues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
181
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(207 citation statements)
references
References 67 publications
25
181
1
Order By: Relevance
“…The CAC decrease with increasing molecular hydrophobicity is the same as in the case of traditional surfactants [38]. This trend is easily understood to know that hydrophobic interaction is an important force in driving the peptide self-assembly, and increase in molecular hydrophobicity would enhance hydrophobic interaction and thus to promote molecular aggregation at lower concentrations [39]. Such a trend could also be rationalized with modified packing parameter equation as presented in our previous work [18].…”
Section: Effect Of the Side Chain Groupsmentioning
confidence: 67%
“…The CAC decrease with increasing molecular hydrophobicity is the same as in the case of traditional surfactants [38]. This trend is easily understood to know that hydrophobic interaction is an important force in driving the peptide self-assembly, and increase in molecular hydrophobicity would enhance hydrophobic interaction and thus to promote molecular aggregation at lower concentrations [39]. Such a trend could also be rationalized with modified packing parameter equation as presented in our previous work [18].…”
Section: Effect Of the Side Chain Groupsmentioning
confidence: 67%
“…[24][25][26][27][28][29] In the former molecule, the di-glycine spacer was included to promote flexibility between the two octapeptides, and the order of amino acids was specifically designed to include a charge repulsion around the central glycine units to minimize any intra-molecular folding of the extended peptide chain (Figure 1), thus enhancing the ability of FEKII18 to co-assemble into two different fibers of FEKII. Prior to any doping experiments, the characteristic self-assembling behavior of the pure FEKII18 peptide was explored and compared to our previous work on the single FEKII peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the Nilsson group has utilized p-p and hydrophobic sidechain interactions to demonstrate the formation of selfassembled materials inspired by amyloid materials. [89][90][91] To set the stage for his future work, Nilsson demonstrated that aromatic residues and p-p stacking interactions were not strictly necessary for amyloid formation with the amphipathic sequence (FKFE) 2 . 89,91 Instead, residues with sufficient hydrophobicity or b-sheet propensity could drive amyloid fibril formation.…”
Section: Amyloid-based Self-assemblymentioning
confidence: 99%
“…[89][90][91] To set the stage for his future work, Nilsson demonstrated that aromatic residues and p-p stacking interactions were not strictly necessary for amyloid formation with the amphipathic sequence (FKFE) 2 . 89,91 Instead, residues with sufficient hydrophobicity or b-sheet propensity could drive amyloid fibril formation. When non-aromatic, highly hydrophobic cyclohexylalanine was substituted for phenylalanine residues, self-assembly still occurred and even exhibited enhanced hydrogelation properties.…”
Section: Amyloid-based Self-assemblymentioning
confidence: 99%